Percepciones de padres de familia de un colegio de Bogotá sobre la importancia de las competencias socioemocionales en las relaciones parentales con sus hijos adolescentes (2023)
Emotional intelligence has managed to demonstrate a regulatory and favorable action in the majority of areas in which it has been incorporated as part of the education and guidance process for adolescents, through the development of socio-emotional competencies, which integrally contribute to satisfactory performance, not only in academic learning, also in personal and social learning, fulfilling several functions among which prevention of risk factors stands out. (Bisquerra 2006).